Does choosing microfluidics for sperm sorting offer an advantage to improve clinical pregnancies in donor egg recipients? - Sapna Srinivas; Suhasini Donthi; Anupama Deenadayal Mettler; Aarti Deenadayal Tolani; Mamata Deenadayal (Wolters Kluwer Medknow Publications, 2022)
Background: Microfluidics (MF), an advanced sperm sorting technology results in the extraction of spermatozoa with higher DNA integrity and lower DNA damage compared to existing conventional sperm sorting methods. Aims: The aim of the present study is to assess the efficiency of MF and to isolate the best spermatozoa for intracytoplasmic sperm injection (ICSI) over the density gradient (DG) technique. Settings and Design: We recruited couples who choose the oocyte donation programme for this study to eliminate confounding factors associated with oocyte quality. Materials and Methods: Sperm was processed by MF (n = 180) and DG (n = 151). ICSI was performed and positive pregnancy, miscarriage and clinical pregnancy rates were compared. Statistical Analysis Used: All variables were analysed using Graph Pad Prism 5. The unpaired two-tailed t-test was used to assess the significance. A value of P < 0.05 was considered statistically significant. Results: There was no significant difference in pregnancy rates between the groups. However, a clear demarcation is seen in terms of clinical pregnancy rates, where the DG group achieved higher clinical pregnancies (91.7%) compared to the MF group (80.7%). Further, we compared miscarriage rates and biochemical pregnancies, and found a significantly higher miscarriage and biochemical pregnancy rate in the MF group (14.5% and 4%, respectively) compared to the DG group (6% and 1%, respectively). Conclusions: Based on the available literature, we anticipated a higher clinical pregnancy rate with MF compared with conventional processing. Our results show MF does not have any add-on positive effect on clinical pregnancy rate.